Revealing Opportunistic Behavior of Village Apparatures in Development of Villages (Study on One Village in Bangkalan District) - Zainal Abidin; Sutikno (Journal of Economics, Business, and Government Challenges, 2018)
This research had a purpose to reveal the opportunistic of behavior from the staff of Village X in their development. This research used an approach of qualitative descriptive divided into two ways observation and interview from the fenomena happens in the real field. From this result analysis data and information, there are findings about the opportunistic behavior of the village apparatus X in the village development that the village apparatus X is related to the main duty and function of only the community service in the field of health and the positive population to society and the impact is not effective on other services. The ineffectiveness of development allocation is only in the physical development but the positive impact on society. Hiding village financial information and allocation of village development so that the community response felt very less related to the number of APBDesa with the development already implemented by the apparatus of Village X.